Construction parameters that affect the air leaks of the envelope in dwellings in Madrid - González-Lezcano, Roberto Alonso; Sanglier Contreras, Gastón; Iglesias Sanz, Carlos Miguel; Sancho Alambillaga, Rocío; López Fernández, Eduardo José (Frontiers in Built Environment, 2023)
In buildings, ventilation, or rather, a lack of airtightness facilitates air leaks, from the outside to the inside and vice versa, and is not controlled. Cold air enters through the enclosure, and warm air is lost to the outdoors, due to the poor hermeticity of the facades, roofs, carpentry, ducts, etc. In order to quantify the airtightness in multi-family dwellings in Madrid, 151 blower door tests have been carried out in multi-family dwellings built in different periods whose execution has been regulated by the UNE-EN 13829 standard. Through its quantification by an n50 value, the average values of 5.8 renovations per hour have been obtained in addition to detecting the main points where air infiltration occurs. The constant improvement in the transmittance of construction elements has indicated that the entry of outside air has a progressively greater relevance to the total energy consumed by the residential sector while facilitating the uncontrolled movement of air through the building envelope. This not only implies higher energy consumption but also generates a series of problems that affect the health of the occupants, such as a lack of thermal comfort, entry of pollutants and odours, noise, inadequate operation of ventilation systems, and less protection against fire.